Profiles of Resilience and Psychosocial Outcomes among Young Black Gay and Bisexual Men. Issue 1 (28th March 2016) - Wilson, Patrick A.; Meyer, Ilan H.; Antebi‐Gruszka, Nadav; Boone, Melissa R.; Cook, Stephanie H.; Cherenack, Emily M.
Abstract: Young Black gay/bisexual men (YBGBM) are affected by contextual stressors—namely syndemic conditions and minority stress—that threaten their health and well‐being. Resilience is a process through which YBGBM achieve positive psychosocial outcomes in the face of adverse conditions. Self‐efficacy, hardiness and adaptive coping, and social support may be important resilience factors for YBGBM. This study explores different profiles of these resilience factors in 228 YBGBM in New York City and compares profiles on psychological distress, mental health, and other psychosocial factors. Four profiles of resilience were identified: (a) Low self‐efficacy and hardiness/adaptive coping (23.5%); (b) Low peer and parental support (21.2%); (c) High peer support, low father support (34.5%); and (d) High father and mother support, self‐efficacy, and hardiness/adaptive coping (20.8%). YBGBM in profile 1 scored markedly higher on distress ( d = .74) and lower on mental health functioning ( d = .93) compared to men in the other profiles. Results suggest that self‐efficacy and hardiness/adaptive coping may play a more important role in protecting YBGBM from risks compared to social support and should be targeted in interventions. The findings show that resilience is a multidimensional construct and support the notion that there are different patterns of resilience among YBGBM.